Structure Activity Relationship of Xanthones for Inhibition of Cyclin Dependent Kinase 4 from Mangosteen (Garcinia Mangostana L.) - Vemu Bhaskar; C. Nauman Mirielle; P. Veenstra Jacob; J. Johnson Jeremy (International Journal of Nutrition, 2019)
The mangosteen fruit is a popular Southeast Asian fruit consumed for centuries. There have been a variety of xanthones isolated from the fruit, bark, roots and leaves with each having unique chemical and physical properties. Previously, the most abundant xanthone α-mangostin has been shown to inhibit CDK4. Herein we describe the role of selected xanthones from the mangosteen inhibiting CDK4. The evidence we provide here is that key functional groups are required to inhibit the CDK4 protein to prevent the phosphorylation of downstream targets critical to inhibiting uncontrolled cell cycle progression. To define the properties of xanthones for inhibiting CDK4 we utilized a cell free biochemical assay to identify inhibitors of CDK4. The following xanthones were used for the analysis: α-mangostin, β-mangostin, γ-mangostin, gartanin, 8-desoxygartanin, garcinone C and garcinone D, 9-hydroxycalabaxanthone, and 3-isomangostin These results further substantiate the unique pharmacological properties of individual xanthones and how a mixture of xanthones may be responsible for a multi-targeted effect in cell based pharmacology systems.
Keywords: cancer